MANAJEMEN STRATEGI UNTUK MENINGKATKAN KUALITAS PENDIDIKAN DI PESANTREN - Munir, Syahrul; Subagyo, Ahmad; Hadi, Muhamad Sofian; Martin, Abraham Yazdi (Idaarah: Jurnal Manajemen Pendidikan, 2025)
Education in Islamic boarding schools has an important role in building the character and knowledge of students. However, amidst the challenges of globalization and technological developments, Islamic boarding schools need to implement effective strategic management to improve the quality of education. This study uses a descriptive qualitative approach with a library research method. Data were obtained from various literature sources such as books, scientific journals, articles and documents relevant to the topic of strategic management in Islamic boarding schools. Data collection techniques were carried out through documentation and content analysis of the sources that had been collected. This study is very important because it touches on the core of improving the quality of religious-based educational institutions that have a vital role in shaping the character, morals, and knowledge of the people. The results of the study show that the application of strategic management of educational institutions has a significant impact on improving the quality of Islamic boarding schools with the implementation of SWOT Analysis in Islamic Boarding School Education.